2022
DOI: 10.21203/rs.3.rs-1272878/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of monocalcium phosphate on the properties of bioactive magnesium phosphate bone cement

Abstract: Background: The bone defects caused by different reasons led to deformity and dysfunction of human body. Considering the need for clinical application, it was essential for bone regeneration to exploit a scaffold with bioactive bone cement. In this paper, we fabricated bioactive magnesium phosphate bone cement (BMPC) at room temperature, then it was set at 37℃ and 100% humidity for 2h. Methods: The process was as follows. MgO was formed by calcining Mg2(OH)2CO3, MgO, KH2PO4 and carboxymethyl chitosan were mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It has been widely used in biological materials, waste treatment, construction materials, etc. [7][8][9][10][11][12][13]. However, in the process of its use, it has been found that magnesium phosphate cement has poor water resistance [9,[14][15][16][17][18]; this greatly restricts its application in many scenarios [9,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used in biological materials, waste treatment, construction materials, etc. [7][8][9][10][11][12][13]. However, in the process of its use, it has been found that magnesium phosphate cement has poor water resistance [9,[14][15][16][17][18]; this greatly restricts its application in many scenarios [9,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%